The Role of Teachers at SMAN 2 Lintau Buo in Utilizing School Information Media - Fitri, Atikah; Pranata, Rudi; Fariq, Aiman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The research aims to find out the role of SMAN 2 Lintau Buo teachers in using school information media. To find out the use of school information media for SMA 2 Negeri Lintau Buo teachers as well as the distribution of school information media for SMA 2 Negeri Lintau Buo teachers.The research method used in this study is that researchers use descriptive qualitative research. While the method used is a descriptive method. .┬á From the results of interviews and observations during the field, the author will explain more about the research that has been done.The results of the research show that the use of school information media based on the theory of diffusion of innovation focuses on the decision and implementation aspects, namely the media used by the SMAN 2 Lintau Buo school in sharing information at school through the school's official account, namely the website and also utilizing social media such as Instagram, Facebook, YouTube.